Small Claims Court Mechanism in Business Dispute Resolution as an Attempt to Apply Fast-Track Basis in the District Courts and its Comparison with Some Countries - Retnaningsih, Sonyendah; Velentina, Rouli Anita (Indonesian Journal of International Law, 2019)
The implementation of Small Claims court mechanism according to Supreme Court Regulation (PERMA) Number 2/2015 concerning Procedures for Small-Claims Court Resolution recently granted a breakthrough in the civil justice system particularly in Indonesia. It was reached by the Supreme Court in order to reduce the court burden against cases with disputes below IDR 200 million rupiah. The disputes resolution by Small Claims court mechanism is done by a single judge assisted with registrar and must completed within 25 working days, the final decision is binding, thus unable to ask for appeal or judicial review. This article tries to comprehend dispute resolution through Small Claims mechanism in several state courts, such as Medan district Court, Palu, and the Jember. The study, also aims to comprehend the comparison of Small Claims mechanism in Indonesia and small claims in the Netherlands and UK in business disputes resolution. The study employs a normative juridical method. Based on the studies, the implementation through Small Claims court mechanism in Indonesia has been carried out in accordance with the Supreme Court Regulation Number 2/2015. Comparison on business dispute resolution using Small Claims court mechanism in Indonesia and in Netherlands and UK proof that the proof mechanisms whether in Indonesia, Netherlands and United Kingdom relatively simple. Legal remedies for Small Claims decision in Indonesia and the verdict in the Netherlands and in England are limited. The distinction is that the case number in Indonesia is higher than the number in the Netherlands and England.